CTL Responses of High Functional Avidity and Broad Variant Cross-Reactivity Are Associated with HIV Control - Mothe, Beatriz; Llano, Anuska; Ibarrondo, Javier; Zamarreno, Jennifer; Schiaulini, Mattia; Miranda, Cristina; Ruiz-Riol, Marta; Berger, Christoph T.; Herrero, M. Jose; Palou, Eduard; Plana, Montse; Rolland, Morgane; et al. (PLoS ONE, 2012)
Cytotoxic T lymphocyte (CTL) responses targeting specific HIV proteins, in particular Gag, have been associated with relative control of viral replication in vivo. However, Gag-specific CTL can also be detected in individuals who do not control the virus and it remains thus unclear how Gag-specific CTL may mediate the beneficial effects in some individuals but not in others. Here, we used a 10mer peptide set spanning HIV Gag-p24 to determine immunogen-specific T-cell responses and to assess functional properties including functional avidity and cross-reactivity in 25 HIV-1 controllers and 25 non-controllers without protective HLA class I alleles. Our data challenge the common belief that Gag-specific T cell responses dominate the virus-specific immunity exclusively in HIV-1 controllers as both groups mounted responses of comparable breadths and magnitudes against the p24 sequence. However, responses in controllers reacted to lower antigen concentrations and recognized more epitope variants than responses in non-controllers. These cross-sectional data, largely independent of particular HLA genetics and generated using direct ex-vivo samples thus identify T cell responses of high functional avidity and with broad variant reactivity as potential functional immune correlates of relative HIV control.